Seasonal and Geographical Transitions in Eukaryotic Phytoplankton Community Structure in the Atlantic and Pacific Oceans - Choi, Chang Jae; Jimenez, Valeria; Needham, David M.; Poirier, Camille; Bachy, Charles; Alexander, Harriet; Wilken, Susanne; Chavez, Francisco P.; Sudek, Sebastian; Giovannoni, Stephen J.; Worden, Alexandra Z. (Frontiers in Microbiology, 2020)
Much is known about how broad eukaryotic phytoplankton groups vary according to nutrient availability in marine ecosystems. However, genus- and species-level dynamics are generally unknown, although important given that adaptation and acclimation processes differentiate at these levels. We examined phytoplankton communities across seasonal cycles in the North Atlantic (BATS) and under different trophic conditions in the eastern North Pacific (ENP), using phylogenetic classification of plastid-encoded 16S rRNA amplicon sequence variants (ASVs) and other methodologies, including flow cytometric cell sorting. Prasinophytes dominated eukaryotic phytoplankton amplicons during the nutrient-rich deep-mixing winter period at BATS. During stratification (‘summer’) uncultured dictyochophytes formed ~35 ± 10% of all surface plastid amplicons and dominated those from stramenopile algae, whereas diatoms showed only minor, ephemeral contributions over the entire year. Uncultured dictyochophytes also comprised a major fraction of plastid amplicons in the oligotrophic ENP. Phylogenetic reconstructions of near-full length 16S rRNA sequences established 11 uncultured Dictyochophyte Environmental Clades (DEC). DEC-I and DEC-VI dominated surface dictyochophytes under stratification at BATS and in the ENP, and DEC-IV was also important in the latter. Additionally, although less common at BATS, Florenciella-related clades (FC) were prominent at depth in the ENP. In both ecosystems, pelagophytes contributed notably at depth, with PEC-VIII (Pelagophyte Environmental Clade) and (cultured) Pelagomonas calceolata being most important. Q-PCR confirmed the near absence of P. calceolata at the surface of the same oligotrophic sites where it reached ~1,500 18S rRNA gene copies ml-1 at the DCM. To further characterize phytoplankton present in our samples, we performed staining and at-sea single-cell sorting experiments. Sequencing results from these indicated several uncultured dictyochophyte clades are comprised of predatory mixotrophs. From an evolutionary perspective, these cells showed both conserved and unique features in the chloroplast genome, with high expression of multiple genes and a selfish element (group II intron) in ENP metatranscriptomes. Comparative analyses across the Pacific and Atlantic sites support the conclusion that predatory dictyochophytes thrive under low nutrient conditions. The observations that several uncultured dictyochophyte lineages are seemingly capable of photosynthesis and predation, raises questions about potential shifts in phytoplankton trophic roles associated with seasonality and long-term ocean change.